Odpowiedź :
Odpowiedź:
Żeby usunąć niewymierność przemnażamy obie strony przez pierwiastek, który jest w mianowniku ułamka:
a) [tex]\frac{1}{\sqrt{3}} * \frac{\sqrt{3} }{\sqrt{3}} = \frac{\sqrt{3} }{3}[/tex]
b) [tex]\frac{2}{\sqrt{5}} * \frac{\sqrt{5}}{\sqrt{5}} = \frac{2\sqrt{5} }{5}[/tex]
c) [tex]\frac{1}{2\sqrt{2} } * \frac{\sqrt{2}}{\sqrt{2}} = \frac{\sqrt{2} }{2*2} = \frac{\sqrt{2}}{4}[/tex]
d) [tex]\frac{2}{3\sqrt{5} } * \frac{\sqrt{5} }{\sqrt{5} } = \frac{2\sqrt{5} }{3*5} = \frac{2\sqrt{5} }{15}[/tex]
e) [tex]\frac{\sqrt{3} }{\sqrt{5} } * \frac{\sqrt{5} }{\sqrt{5} } = \frac{\sqrt{15} }{5}[/tex]
f) [tex]\frac{4\sqrt{2} }{\sqrt{3} } * \frac{\sqrt{3} }{\sqrt{3} } = \frac{4\sqrt{6} }{3}[/tex]
Szczegółowe wyjaśnienie: